Characterization of a Truncated Metabotropic Glutamate Receptor in a Primitive Metazoan, the Parasitic Flatworm Schistosoma mansoni - Taman, Amira (Public Library of Science, 2011)

(untitled)
A novel glutamate-binding protein was identified in Schistosoma mansoni. The protein (SmGBP) is related to metabotropic glutamate receptors from other species and has a predicted glutamate binding site located within a Venus Flytrap module but it lacks the heptahelical transmembrane segment that normally characterizes these receptors. The SmGBP cDNA was cloned, verified by 5′ and 3′ Rapid Amplification of cDNA Ends (RACE) and shown to be polyadenylated at the 3′end, suggesting the transcript is full-length. The cloned cDNA was subsequently expressed in bacteria and shown to encode a functional glutamate-binding protein. Other studies, using a specific peptide antibody, determined that SmGBP exists in two forms, a monomer of the expected size and a stable but non-covalent dimer. The monomer and dimer are both present in the membrane fraction of S. mansoni and are resistant to extraction with high-salt, alkaline pH and urea, suggesting SmGBP is either an integral membrane protein or a peripheral protein that is tightly associated with the membrane. Surface biotinylation experiments combined with western blot analyses and confocal immunolocalization revealed that SmGBP localized to the surface membranes of adult male schistosomes, especially the dorsal tubercles. In contrast, we detected little or no expression of SmGBP either in the females or larval stages. A comparative quantitative PCR analysis confirmed that the level of SmGBP expression is several-fold higher in male worms than cercariae, and it is barely detectable in adult females. Together, the results identify SmGBP as a new type of schistosome glutamate receptor that is both gender- and stage-specific. The high-level expression of this protein in the male tubercles suggests a possible role in host-parasite interaction.